Identification of Two de novo Variants of CACNA1A in Pediatric Chinese Patients With Paroxysmal Tonic Upgaze - Zhang, Li-Ping; Jia, Yu; Wang, Yu-Ping (Frontiers in Pediatrics, 2021)
Objective: Investigate the clinical manifestations and genotypes of paroxysmal tonic upgaze (PTU) in Chinese children. Patients and Methods: We report clinical manifestations and genetic test results of 4 pediatric PTU patients in China. Recent articles on PTU cases are also summarized and analyzed. Results: The onset age of all four cases was at early infancy and they presented as episodic binocular upward gaze with mild growth retardation. Two patients each carried a novel de novo variant in the CACNA1A gene, c.4046C>T (p.R1349X) and c.4415C>T (p.S1472L). Conclusion: Patients with infantile-onset paroxysmal binocular upward gaze should be considered to diagnose as PTU.